Identifying priorities for cancer caregiver interventions: protocol for a three-round modified Delphi study. Issue 2 (13th February 2019) - Blaschke, Sarah-May; Lambert, Sylvie D; Livingston, Patricia M; Aranda, Sanchia; Boltong, Anna; Schofield, Penelope; Chambers, Suzanne K; Krishnasamy, Meinir; Ugalde, Anna
Abstract : Introduction: Cancer is often considered a chronic disease, and most people with cancer have a caregiver, often a family member or friend who provides a significant amount of care during the illness trajectory. Caregivers are frequently in need of support, and a range of interventions have been trialled to improve outcomes. Consensus for optimal ways to support caregivers is not known. The aim of this protocol paper is to describe procedures for a modified Delphi study to explore expert consensus about important factors when developing caregiver interventions. Methods and analysis: Online modified Delphi methodology will be used to establish consensus for important caregiver intervention factors incorporating the Patient problem, Intervention, Comparison and Outcome framework. Round 1 will comprise a free-text questionnaire and invite the panel to contribute factors they deem important in the development and evaluation of caregiver interventions. Round 2 is designed to determine preliminary consensus of the importance of factors generated in round 1. The panel will be asked to rate each factor using a 4-point Likert-type scale. The option for panellists to state reasoning for their rating will be provided. Descriptive statistics (median scores and IQR) will be calculated to determine each item's relative importance. Levels of consensus will be assessed based on a predefined consensus rating matrix. In round 3, factors will be recirculated including aggregate group responses (statistics and comment summaries) and panellists' own round 2 scores. Panellists will be invited to reconsider their judgements and resubmit ratings using the same rating system as in round 2. This will result in priority lists based on the panel's total rating scores. Ethics and dissemination: Ethics for this study has been gained from the Deakin University Human Ethics Advisory Group. It is anticipated that the results will be published in peer-reviewed journals and presented in a variety of forums.